Repositioning Undergraduate Education in Recreation and Leisure Studies. Issue 1 (2nd January 2018) - Pitas, Nicholas; Hickerson, Benjamin; Murray, Alison; Newton, Jennifer
ABSTRACT: This article applies the repositioning framework developed for recreation and leisure service providers (Crompton, 2000, 2009) to recreation and leisure studies as an academic field. To ensure the viability of recreation and leisure studies, internal stakeholders must raise the standing of the field among several key external stakeholder groups: prospective undergraduate students and their parents, university administration, professionals, and the general public. The repositioning framework functions by identifying socially and politically relevant issues, working to address those issues through the medium of recreation and leisure studies, and effectively communicating these potential contributions to a variety of audiences. This article outlines real, associative, and psychological repositioning strategies that academic departments may implement individually, and as a collective whole, to raise the standing of recreation and leisure studies as a field of study.